Bevacizumab for symptomatic radiation‐induced tumor enlargement in pediatric low grade gliomas. Issue 2 (8th November 2014) - Foster, Kimberly A.; Ares, William J.; Pollack, Ian F.; Jakacki, Regina I.
<x xml:space="preserve">Abstract</x> Background Radiation therapy (RT)‐induced effects in children treated for low grade glioma (LGG) can result in worsening of neurologic symptoms and clinical and radiographic deterioration. Treatment for radiation‐induced tumor enlargement is based on symptom control and usually involves steroids. Procedure We conducted a retrospective review of children with LGG treated with RT who developed symptomatic radiation‐induced tumor enlargement and were managed with bevacizumab. Charts were abstracted for onset and duration of RT changes, toxicity and doses of dexamethasone and bevacizumab. Tumor volumes prior to RT, at maximal size following RT, after bevacizumab administration, and at follow‐up were evaluated. Results Five children were treated with bevacizumab for symptomatic radiation‐induced tumor enlargement following RT for LGG at a median of 4.2 months (range, 1–11 months) after completion of RT. The median increase in volume of tumor was 195.4% (range, 115.5–309%) compared to the pre‐RT volume. Bevacizumab 5–10 mg/kg was administered IV q 2–4 weeks as primary treatment (n = 1) or to assist in weaning patients off steroids (n = 4). All children on high dose steroids (n = 4) were weaned off or to physiologic doses of hydrocortisone. Two children developed avascular necrosis after prolonged steroid use and while on bevacizumab. Radiographically, all children showed significant improvement and are now a median of 31 months (range, 18–50 months) from the completion of radiation without requiring additional tumor‐related therapy. Conclusions Bevacizumab can play an important role in children with symptomatic radiation changes following LGG treatment, allowing patients to avoid or minimize the toxicity of long‐term steroid use. Pediatr Blood Cancer 2015;62:240–245. © 2014 Wiley Periodicals, Inc.